Utilitarian sensibility and liberal education: the case of London University, 1825-36 - Mohd Sobri, Mohd Helmi (Blackwell Publishing Ltd, 2019)
This article re-examines the utilitarian character of London University during its foundational years between 1825 and 1836. Previous historians have evaluated the utilitarian character of the institution in terms of whether or not it was influenced by Jeremy Bentham and his philosophy. This approach, however, overlooks the fact that the contemporary sense of being utilitarian was much richer than, and autonomous from, Benthamite utilitarianism. It was a cultural sensibility rather than a systematic philosophy. The eighteen-twenties witnessed the rise of this sensibility. The founders of the new university significantly benefited from this atmosphere as they could define their cause and criticize their opponents in its terms.